Windows 2000 server system administration handbook. - Syngress Media, Inc. (Rockland, Mass. : Syngress Media, 2000)
Many organizations and network administrators are looking for information on Windows 2000 and its new features. IT professionals responsible for installing, configuring, and managing Microsoft products will be highly motivated to migrate to this new technology, based on its promise of reducing administrative overhead. Windows 2000 Server System Administration Handbook will help NT4 professionals to administer and support the Windows 2000 Server operating system. NT administrators will be able to differentiate the features and technology changes from Windows NT 4.0 to Windows 2000. In the handbook, readers will find a complete overview of the product, catered to their needs. * This book coincides with the launch of Windows 2000 Server, the host system for the product. * Includes the following: * Detailed coverage of Active Directory, Microsoft Management Console, and new Windows 2000 hardware support * Implementing new Windows 2000 security options * Upgrading a network to Windows 2000.
Includes index.
Keywords: Microsoft Windows server; Operating systems (Computers).; Electronic books